Transparent things [compact disc] - Ford, Gia (Chrysalis Records, 2024)
The debut album from rising artist-to-watch Gia Ford is an eclectic collection of indie-pop songs with thoughtful depth. Produced by Tony Berg (Boygenius, Phoebe Bridgers) and co-written with Liam Howe (Adele, Lana Del Rey, MARINA), each track is meant to depict a different character who is outcast. These songs explore issues of feeling alienated, frustrations with society, and a hopeful romantic longing aided by plenty of charisma.